Anketa o poznavanju tujih izrazov v medicini - Manohin, Aleksander (Zdravstveno varstvo, 2004)
A survey conducted among the sixth-grade medical undergraduates of the Division of Medicine, Medical Faculty,Ljubljana, showed that the students had poor knowledge of foreign words and medical jargon: they tended to misunderstand many of these expressions or were not familiar with them at all.The author suggests that some changes should be made in the basic undergraduate curriculu, with more emphasis being placed on foreign and jargonmedical expressions, used in daily communication.
Keywords: linguistics; lingvistika; medicina; medicine; Slovene; slovenščina; strokovni jezik; terminologija; terminology